(untitled) (Research, Society and Development, 2021)
The purpose of this article is to compare advantages and disadvantages of deploying solar panels and green roofs in residential coverages. The aim is to support decision-making, where the architectural design has reduced area, or limit investment, being necessary to choose between the two types. The study is based on the conceptual understanding of green infrastructure and ecosystem services. The object of study is the design of a house, with a coverage area of 100 m², located in the city of Ilhéus - Bahia - Brasil, as well as the city’s infrastructure and market characteristics. The research uses the comparative method, and has as parameters: implementation cost; maintenance requirements; efficiency; ecosystem services obtained; necessary care and aspects of insertion in the project and the landscape. Bibliographic data and market research are used. As a result, it appears that, in general, the choice between typologies can vary according to the principles of architectural design.